Chapter 13 Ageism in the Health Care System: Providers, Patients, and Systems (2018)
Older adults are major consumers of health care. Within the context of an ageing society, their presence in the health care system will continue to grow. Ageist stereotypes and discrimination against older adults have an impact on the health and well-being of older citizens and are potential barriers to health equality. This chapter addresses ageism at different levels of the health care setting with a review of empirical research and health care policy. At the micro (personal) level, manifestations of ageism include attitudes toward older adults among physicians, nurses, and other health care professionals. Ageist communication styles used with older patients, age-biased clinical decision-making regarding diagnostics and treatments, and self-directed ageism in older patients are also discussed. Macro-level (institutional or structural) aspects of ageism are then examined, as reflected in health care reimbursement structures, participation of older adults in clinical trials, institutional policies governing care, and the lack of emphasis on geriatric-specific training for health care professionals. The chapter closes with an integration of the findings and a discussion of the challenges in identifying and reducing ageism in this setting. Conclusions are drawn and recommendations for future research and practice are made.